REVITALISASI HUKUM ADAT SEBAGAI SUMBER HUKUM DALAM MEMBANGUN SISTEM HUKUM INDONESIA - Lastuti Abubakar (Faculty of Law, Universitas Jenderal Soedirman, 2013)
The existence of adat law as a legal source has been neglected. Due to the thinking that Adat Law has traditional nature and has no ability adapt with modern life. Hence it necessary to fnd relevant Adat law to cope problems of Indonesia within globalization era. It is important to know the urgency of adat law as foundation of national legal development policy. This research was conducted through analitycal descriptive methods with normative juridical approach.data were collected through literature research that were analyzed qualitatively through juridical interpretation based on relations between legal principles, norms as well theories within phenomenon in the society. Research shows that adat law as institution (heritage, indigenous rights, pawn, rent, production sharing.etc) still relevant with national legal development. Partially, those institutions had been codified within national legislations. In addition, it may also become such inspiration the national legal development in regards to finding of law.Key words: revitalization, adat law, source of law Baca secara foneti